Analisis Profil Pelajar Rahmatan Lil ‘Alamin dalam Buku Tunjuk Ajar Melayu Karya Tenas Effendy dan Relevansinya dengan Pendidikan Agama Islam - Zupi, Zupi; Alwizar, Alwizar; Ehulawa, Djeprin (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2025)
This study aims to analyze the values of the Rahmatan Lil 'Alamin Student Profile in Tunjuk Ajar Melayu by Tenas Effendy and its relevance to Islamic Religious Education. The background of this research is based on the importance of strengthening students' character within the Merdeka Curriculum, which emphasizes the development of universal values aligned with Islamic teachings. This research is a library study using a qualitative descriptive approach. The results show that there is a harmony between the values of the Rahmatan Lil 'Alamin Student Profile and the teachings in Tunjuk Ajar Melayu. Values such as civility, exemplary behavior, nationalism, moderation, balance, integrity and firmness, equality, deliberation, tolerance, dynamism, and innovation are reflected in Tunjuk Ajar Melayu by Tenas Effendy, rooted in Malay culture and Islamic values. These values have strong relevance to Islamic Religious Education, in terms of its foundations, functions, and educational goals. Tunjuk Ajar Melayu can serve as an alternative source for developing character education based on local wisdom, in harmony with the vision of national education and the principles of Islam as rahmatan lil ‘alamin (a mercy to all creation).